Varietal Preferences of Major Insect Pests of Okra (Abelmoschus esculentus L. Moench.) - , Arti Sharma, R. K. Meena, Ram Narayan Sharma, Heera Kumari, Jyoti Sharma, Bablu Sharma (Archives of Current Research International, 2025)
Aims: To evaluate the resistance of 12 okra varieties to major insect pests, including sucking pests and shoot and fruit borers, under natural infestation conditions in Rajasthan. Study Design: A Randomized Block Design with three replications was used to screen twelve okra varieties for resistance to major insect pests. Each plot measured 2.25 x 1.5 m², with 45 cm row spacing and 30 cm plant spacing. Place and Duration of Study: The investigations were conducted during the Kharif season of 2022 at the Horticulture Farm, S.K.N. College of Agriculture, Jobner. Methodology: In this study, natural infestation of insect pests was observed from germination to harvest, with weekly population counts. Sucking pests (leafhoppers and whiteflies) were counted early in the morning on five tagged plants per plot, using absolute counting on three leaves (top, middle, bottom). Shoot and fruit borer (Earias spp.) infestations were recorded starting two weeks after sowing. The percent infestation was calculated by comparing infested shoots and fruits with healthy ones. Results: In this study, twelve okra varieties were screened for resistance to major pests, including leafhopper (Amrasca biguttula biguttula), whitefly (Bemisia tabaci), and shoot and fruit borer (Earias spp.). For leafhopper resistance, varieties DOV-77, DOV-17, and 6126 were least susceptible, while Punjab Suhavani and Pusa Bhindi-5 were highly susceptible. Moderately susceptible varieties included Arka Abhay, DOV-66, Pusa Sawani, Kashi Kranti, PS, Arka Anamika, and A-4. In the case of whitefly, DOV-77 and DOV-17 were least susceptible, whereas A-4 and Punjab Suhavani were most susceptible. Moderately susceptible varieties were 6126, DOV-66, Arka Abhay, PS, Pusa Sawani, Kashi Kranti, Arka Anamika, and Pusa Bhindi-5. Regarding shoot and fruit borer resistance, DOV-66 and 6126 exhibited the least susceptibility to shoot infestation, while Pusa Bhindi-5 and Pusa Sawani were highly susceptible. For fruit infestation, PS and A-4 were least susceptible, while Pusa Sawani and Arka Abhay were highly susceptible. Conclusion: The study identifies promising okra varieties with varying levels of resistance to key pests, including leafhopper, whitefly, and shoot and fruit borer. DOV-77, DOV-17, and 6126 showed the least susceptibility to leafhopper and whitefly, while DOV-66 and 6126 exhibited reduced shoot infestation. Pusa Bhindi-5 and Pusa Sawani were found to be highly susceptible to several pests. These findings offer valuable guidance for selecting resistant varieties for integrated pest management in okra cultivation.